Illocutionary Acts in Joaquin Phoenix’s Acceptance Speeches at Film Awards Ceremonies in 2020: A Pragmatic Study - Ervina CM Simatupang; Muhamad Fajar Ibrahim (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This research aims to identify the types of illocutionary acts, to analyze the functions of illocutionary acts, and to describe the strategies of illocutionary acts used in Joaquin Phoenix’s acceptance speeches at five film awards ceremonies in 2020. The method used in this research is qualitative methodology which, according to Taylor (2016), produces descriptive data—people’s own written or spoken words and observable behavior. The theoretical framework for this research refers to: Searle’s (1979) theory on types of illocutionary acts, Leech’s (1993) theory on functions of illocutionary acts, and Yule’s (1996) theory on strategies of illocutionary acts. Out of 30 analyzed data, the research shows that: there are 11 expressive types (37%), 10 assertive types (33%), 6 directive types (20%), and 3 commissive types (10%); there are 14 convivial functions (47%), 8 collaborative functions (27%), 6 competitive functions (20%), and 2 conflictive functions (6%); there are 14 direct strategies (47%) and 16 indirect strategies (53%).